The role of Exchange Rates in non-oil export activity: evidence from Azerbaijan - Ganbarov, Fuad; Alieva, Gunay; Babazade , Isgender (Journal of Eastern European and Central Asian Research (JEECAR), 2020)
The dependence of the Azerbaijani economy on oil makes urgent the issue of diversifying the economy to increase its competitiveness. This, in turn, necessitates the formation of techniques to qualitatively assess the effectiveness of diversification to alternative, namely non-oil exports. This study aims to develop an econometric model to assess the impact of non-oil export diversification on Azerbaijan’s economic development. Based on the literature analysis and using hierarchy analysis by T. Saaty, a list of indicators has been proposed to assess the diversification of non-oil exports. The opinions of 30 experts were used to prioritize the indicators. An integral coefficient of diversification of non-oil exports was modelled based on an additive convolution of diversification indicators, taking into account the coefficients of their significance and expert assessments. The research results can serve as a suggestion as to the formation of an effective strategy for the modernization of the country’s economy.